Dropout Percentage of Scheduled Caste and Scheduled Tribe Children in India A Decadal Analysis up to Secondary Level - Pandita, Ramesh (JOURNAL OF INDIAN EDUCATION, 2015)
The present study seeks to examine the enrolment and the dropout percentage of Scheduled Caste (SC) and Scheduled Tribe (ST) children in India. The study is supported by empirical findings based on the analysis of secondary data retrieved from the official website of the Ministry of Human Resource Development, Government of India, for the period 2001-02 to 2010-11. The enrolment and dropout percentage of SC/ST children have been studied separately for the boys and the girl at three stages viz., primary, upper primary and secondary level. SC and ST are the two largest socially disadvantaged sections of Indian society. During the period of study, the overall enrolment percentage of SC and ST children have increased by 37.49 per cent and 37.92 per cent and their average annual dropout percentage has declined by 3.27 per cent and 2.23 per cent respectively. Among SC children, compared to 51.41 per cent boys, 52.16 per cent girls dropped out annually, while as among ST children, compared to 59.87 per cent boys, 61.32 per cent girls dropped out annually. Nearly 68.21 per cent ST and 62.57 per cent SC children drop out by the time they reach upper primary level and 88.17 per cent ST children and 83.62 per cent SC children dropped out by the time they reach secondary level. There is a need to observe caution while generalising the findings, especially while co-relating them to other sections of the Indian society.